Effect of COVID-19 on Undergraduate Medical Education: A Letter from Pakistan - Muhammad Fazal Hussain Qureshi; Muzna Shah; Mahira Lakhani (ziauddin University, 2024)
Dear Editor First identified in Wuhan, China, on December 31 2019, coronavirus spread like bush fire. The WHO declared it as a Global Pandemic on March 11 2021. COVID-19 was termed novel based on newly identified pathogens, thus leading to a state of uncertainty regarding treatment and prevention1. This virus can present with an array of symptoms; dry cough, breathlessness, chest pain, myalgia, and diarrhea2. Undergraduate medical education has shifted to virtual learning systems to halt the transmission of the virus. This letter elaborates on the challenges faced and the impact of COVID-19 on the life of undergraduate medical students.